'Scrutinised, judged and sabotaged': A qualitative video diary study of first-time breastfeeding mothers. (August 2019) - Taylor, Alison M.; Teijlingen, Edwin van; Ryan, Kath M.; Alexander, Jo
Abstract: Objective: To explore how support impacted on mothers' breastfeeding experiences in the first few weeks following birth. Design: A qualitative approach explored real-time experiences of breastfeeding captured by five first-time mothers in the South of England on camcorder as video diaries. A multi-dimensional approach involving thematic analysis ensured both the audio and visual elements of the data were analysed. Findings: Mothers felt 'under surveillance' by the biomedical approach to support from the healthcare team. At best mothers felt reassured that they were 'on the right track'. When mothers felt their breastfeeding was constantly being examined, criticised and threatened they felt 'scrutinised, judged and sabotaged'. When they found it difficult to access healthcare support, or they avoided it altogether to circumvent further scrutiny, they felt 'abandoned and alone'. Key conclusions: Collecting audio-visual data in real-time adds fresh insights into how support impacts mothers' experiences of breastfeeding. The biomedical approach to support for breastfeeding is not effective. Scrutinising, judging and/or sabotaging mothers' attempts to breastfeed can have long-lasting effects on maternal emotional wellbeing. Implications for practice: Breastfeeding support might be improved by adopting a more social model of care. Future research needs to explore how relationship-based support can be provided by the health service.